THE ROLE OF STRATEGIST MANAGER AND EVENT MANAGER IN “TILIK JIWA” CAMPAIGN STRATEGY TO INCREASE AWARENESS AND PARTICIPATION IN MENTAL HEALTH SCREENING BY DINAS KESEHATAN KOTA SEMARANG - Bilghis Savita; Lintang Ratri Rahmiaji (Interaksi Online, 2026)
Mental health remains a taboo topic in society. This is especially true for the younger generation, who still have low levels of awareness and knowledge, as well as stigma in society towards mental health screening services. In the city of Semarang, particularly in the Banyumanik and Tembalang districts, this has become one of the main causes of low community participation in mental health screening services. To overcome this particular obstacle, the Tilik Jiwa campaign was developed in collaboration with Dinas Kesehatan Kota Semarang to increase community awareness and participation in mental health screening services. The strategy for the Tilik Jiwa campaign was designed based on 3 conceptual frameworks. This strategy was designed based on the situation analysis of 236 respondents. The implementation of the strategy increased awareness by 87.79 percentage points, knowledge by 89.33 percentage points, and reduced the level of stigma towards mental health screening services to only 12.3%. In addition, the Tilik Jiwa campaign succeeded in increasing overall participation by 36% or 86 people. These results indicate that the communication strategy and the implementation have become an integrated and effective communication strategy.